APPLICATION OF PACS DATA SECURITY MODEL ON RADIOLOGY UNIT RECOMMENDATIONS FOR PACS DATA SECURITY MODEL IN RADIOLOGY INSTALLATIONS - Gatot Murti Wibowo; Yessi Widhianasari; Agung Nugroho Setiawan; Mega Indah Puspita; Bryan Ilham Pranandya (Poltekkes Kemenkes Semarang, 2024)
Data security is an important issue in an organization, proper information security management is a continuous process of building and maintaining programs, policies and controls to protect information. Management must maintain the confidentiality, integrity and availability of patient information in accordance with ISO/IEC 27002 and HIPAA standards. However, health institutions lack processes for data security, so a simple method is needed that can be done by the Radiology installation itself.The method used in this case is to observe the ISO/IEC 27002 and HIPAA references and then make steps that can be implemented. The Radiology Installation can create a simple protocol that can be adhered to to meet existing standards. Protocols that meet the standards that can be fulfilled by Radiology Installations are the categories of authentication, confidentiality, data integrity, non-repudiation and access control.A simple protocol that can be created and implemented is a protocol that discusses access rights, user name, computer usage log book containing a data base, providing a strong password that only the user knows, regular data backup using password encryption, storage location. locked archives, surveillance cameras if possible and computer use for other purposes should be avoided. By creating simple security protocols at the radiology installation level, the radiology team has tried to comply with ISO 27002 and HIPPA.Â